Prognostic Value of Combination of Hemodynamic Parameters in Asymptomatic Aortic Valve Stenosis—The COFRASA/GENERAC Study. Issue 1 (4th March 2017) - Mathieu, Tiffany; Nguyen, Virginia; Cimadevilla, Claire; Melissopoulou, Maria; Codogno, Isabelle; Verdonk, Constance; Duval, Xavier; Tubiana, Sarah; Arangalage, Dimitri; Vahanian, Alec; Messika-Zeitoun, David
ABSTRACT: Background: Whether risk-stratification in aortic valve stenosis (AS) should rely on a single hemodynamic parameter or a combination of hemodynamic parameters is still debated. We aimed to evaluate the prognostic value of mean pressure gradient (MPG), aortic valve area (AVA), and the dimensionless index (DI) in patients with AS and to test whether their combination provides additional prognostic information. Methods: We enrolled 319 asymptomatic patients with AS (90 mild, 173 moderate, and 56 severe AS). All patients were prospectively followed on a yearly basis and AS-related events (sudden death, heart failure, or new onset of AS-related symptoms) were collected. Results: After a mean follow-up of 3.1±1.7 years, an AS-related event occurred in 84 patients (26%). When considered in isolation, after adjustment for age, sex, history of coronary artery disease, valve anatomy, and left ventricular ejection fraction, each parameter (MPG, AVA, and DI) independently predicted the occurrence of AS-related events (all p<0.0001). When considered in combination, MPG and AVA (p=0.0009 and p<0.0001 respectively) or MPG and DI (p=0.0001 and p<0.0001 respectively) remained independent predictors of outcome. Results were sustained after exclusion of 31 patients (10%) with discordant grading. Conclusion: In a large prospective cohort of asymptomatic patients with a wide range of AS severity, AVA, MPG, and DI were all important prognostic factors. More importantly, irrespective of the presence of patients with discordant grading, MPG and either the AVA or the DI provided complementary prognostic information. Our results show that these hemodynamic parameters should be considered in combination in the clinical management of AS patients.